La fonction expressive des points de suspension dans le texte littéraire moderne - Хайчевська, Тетяна Миколаївна; Khaichevska, Tetiana M. (Національний університет "Острозька академія", 2015)
Le rôle de la ponctuation dans le texte littéraire moderne acquiert de plus en plus une grande importance. L'utilisation des signes de ponctuation passe à un nouveau niveau et devient pour l'auteur un outil supplémentaire d'expression et d’influence sur la perception d’une œuvre littéraire par le lecteur. Leur expressivité, la capacité de rendre le texte plus expressif et vif, et même intéressant pour le lecteur sont manifestées en conditions de l'usage original et non-normatif. Dans cet article, on tente de décrire la fonction expressive des points de suspension, parce que ce signe de ponctuation est le plus souvent utilisé par les écrivains français pour transmettre par écrit une variété de particularités phonétiques et nuances du sens complémentaires. Роль пунктуації у сучасному художньому тексті набуває усе більшого значення. Використання пунктуаційних знаків переходить на якісно новий рівень і стає додатковим інструментом самовираження та впливу автора на сприйняття художнього твору читачем. В умовах оригінального та ненормативного застосування проявляється їхня експресивність, здатність увиразнювати художній текст, робити його більш яскравим та цікавим для читача. У статті зроблено спробу описати експресивну функцію трикрапки, оскільки саме цей пунктуаційний знак найчастіше використовується французькими письменниками для передачі різноманітних додаткових фонетичних та смислових відтінків на письмі. The importance of punctuation in modern fiction text has continuously being growing up. The use of punctuation marks has been moving to a new level and becoming an additional author’s tool of self-expression and influence on the reader’s perception of the work. In this article an attempt is made to observe and describe the expressive function of ellipsis, because this punctuation mark is most often used by French writers to express a variety of additional phonetic peculiarities and nuances of the sense in writing. The results of investigation have shown that it is in the context of original or non-normative use, where the ellipsis manifests its expressiveness and obtains an ability to make a fiction text clearer, more vivid and interesting for the reader. The expressive function of ellipsis is based on its capacity to replace most punctuation marks and different parts of the utterance. This punctuation mark can express in writing the character’s exited or emotional speech, the process of reflection, the wordplay; create comic effect, etc. Besides, the ellipsis is often used in combination with exclamation and question marks to intensify the effects of astonishment or embarrassment. The lines of points can denote author’s allusion that enables the reader to guess what is meant. It has been revealed that punctuation variation indirectly draws the reader’s attention to the novelty and importance of a raised problem and underlines the unique vision of the author.
Експресивна функція трикрапки в сучасному художньому тексті
Keywords: la ponctuation; les points de suspension; la fonction expressive; l’expressivité des points de suspension; la variation de ponctuation; пунктуаційний знак; трикрапка; низка крапок; експресивна функція; експресивність трикрапки; пунктуаційне варіювання; punctuation mark; ellipsis; expressive function; expressiveness of ellipsis; punctuation variation